Psychiatric Hegemony A Marxist Theory of Mental Illness - Cohen, Bruce M. Z.; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book offers a comprehensive Marxist critique of the business of mental health, demonstrating how the prerogatives of neoliberal capitalism for productive, self-governing citizens have allowed the discourse on mental illness to expand beyond the psychiatric institution into many previously untouched areas of public and private life including the home, school and the workplace. Through historical and contemporary analysis of psy-professional knowledge-claims and practices, Bruce Cohen shows how the extension of psychiatric authority can only be fully comprehended through the systematic theorising of power relations within capitalist society. From schizophrenia and hysteria to Attention-Deficit Hyperactivity Disorder and Borderline Personality Disorder, from spinning chairs and lobotomies to shock treatment and antidepressants, from the incarceration of working class women in the nineteenth century to the torture of prisoners of the 'war on terror' in the twenty-first, Psychiatric Hegemony is an uncompromising account of mental health ideology in neoliberal society.
Chapter 1 Introduction: Thinking Critically about Mental Illness -- Chapter 2 Marxist Theory and Mental Illness: A Critique of Political Economy -- Chapter 3 Psychiatric Hegemony: Mental illness in Neoliberal Society -- Chapter 4 Work: Enforcing Compliance -- Chapter 5 Youth: Medicalising Deviance -- Chapter 6 Women: Reproducing Patriarchal Relations -- Chapter 7 Resistance: Pathologising Dissent -- Chapter 8 Conclusion: Challenging the Psychiatric Hegemon -- Chapter Appendix 1: Methodology for Textual Analysis of the DSMs -- Chapter Appendix 2: Youth-Related Diagnostic Categories in the DSM, 1952-2013 -- Chapter Appendix 3: 'Feminised' Diagnostic Categories in the DSM, 1952-2013.
Keywords: Psychology, Clinical; Social medicine; Psychiatry; Psychology, Pathological